The effects of iron supplementation on hemoglobin levels of some anemic Filipino children below 13 years old in General Emilio Aguinaldo, Cavite - Panomratanarak, Benya
This study was conducted to determine the effects of iron supplementation (ferrous sulfate) on the hemoglobin levels of some anemic Filipino children aged 1-13 years oln in Gen. Emilio Aguinaldo, Cavite. The response effects of supplementation were also tested among these anemic Filipino children with or without hookworm infection. Anemia status was determined by hemoglobin and hematocrit levels using the AO hemoglobinometer and Guest-Weishelbaun methods, respectively; while hookworm status was determined by the Kato-katz modified thick and smear technique. The study population comprised the anemic children categorized as positive and negative to hookworm infection. The subjects in each category were randomly allocated into experimental and control groups depending on the type of treatment as, iron treatment as, iron or placebo, respectively. Iron supplements were given at doses of 15, 45 and 60 mg elemental iron for the age groups 1-3, 4-6 and 7-13 years, respectively. Placebo was in the form of honey for the 1-6 year olds and chocolate candy for the 7-13 year olds. Iron supplements or placebo were administered to the subjects by their respective parents for a period of 2 months. Hemoglobin and hematocrit levels were periodically determined 30 and 60 days treatment. Increasing hemoglobin and hematocrit levels were observed as the duration of treatment lengthened for the iron-treated children with positive or negative hookworm infection. However, no significant differences between the 2 groups of children with or without hookworm were found when their hemoglobin and hematocrit levels were compared. Among the placebo-treated children with or without hookworm, no significant increases in the hemoglobin and hematocrit levels were found ad the duration of treatment increased. Significant differences between the hemoglobin levels of the iron-treated and placebo-treated children at different periods were observed. The findings of the present study revealed that the magnitude of response to the iron supplementation at the different periods of treatment was manifested in the increase in hemoglobin levels of both the hookworm and non-hookworm infected anemic children. This study also showed the importance of iron supplementation in improving the anemia status of the children wherein the management could possibly be done in their respective homes.